2012
DOI: 10.4103/0971-6580.97199
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative potential of Psidium guajava on hemato-biochemical alterations in arsenic-exposed Wistar rats

Abstract: The present study attempts to investigate the effects of Psidium guajava (P. guajava) when administered in combination with sodium arsenite @ 20 ppm in drinking water with the aim of achieving normalization of altered biochemical, hematological parameters suggestive of hepatic damage and depletion of inorganic arsenic following chronic arsenic exposure. Thirty adult Wistar rats were given 20 ppm arsenic for eight weeks along with hydro alcoholic leaf extract of P. guajava at a dose of 100 mg/kg body weight wt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The reason for such reversal is difficult to explain since histopathological alterations as well as induction of apoptosis was observed in the same treatment group. The increased SGOT and SGPT levels in rat after 45 days treatment of 10 ppm sodium arsenite was also described by Tandan et al [ 47 ], whereas Santra et al [ 45 ] reported increased SGOT and SGPT levels after 12 months of arsenic treatment at 3.2 ppm in mice. Liver alteration in histopathological architecture was evident mainly in the form of loss of integrity of central vein, loss of hepatic cord organization, and dose and time dependent vacuolation which corroborates with earlier studies [ 45 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 66%
“…The reason for such reversal is difficult to explain since histopathological alterations as well as induction of apoptosis was observed in the same treatment group. The increased SGOT and SGPT levels in rat after 45 days treatment of 10 ppm sodium arsenite was also described by Tandan et al [ 47 ], whereas Santra et al [ 45 ] reported increased SGOT and SGPT levels after 12 months of arsenic treatment at 3.2 ppm in mice. Liver alteration in histopathological architecture was evident mainly in the form of loss of integrity of central vein, loss of hepatic cord organization, and dose and time dependent vacuolation which corroborates with earlier studies [ 45 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 66%
“…There are several types of herbal-based chelators have been used as the arsenic antidote such as Cucumis Sativus [39], curcumin [40], green tea [41], and Psidium guajava [42].…”
Section: Discussionmentioning
confidence: 99%
“…The increase of creatinine concentration might be due to the loss of of kidney function and considered as functional evidence of arsenic-induced nephrotoxicity. [ 24 25 26 ] There was a decrease in serum albumin in rats of group I compared to the control group which might be due to the severe nephrotoxic effect of arsenic resultinga drainage of protein through urine. There was a significant decrease in BUN and creatinine levels in the Tephrosia–treated (group II) animals [ Table 1 ] with respect to group I.…”
Section: Discussionmentioning
confidence: 99%